Everolimus in Pancreatic Neuroendocrine Carcinomas G3. Issue 3 (March 2017) - Panzuto, Francesco; Rinzivillo, Maria; Spada, Francesca; Antonuzzo, Lorenzo; Ibrahim, Toni; Campana, Davide; Fazio, Nicola; Delle Fave, Gianfranco
Abstract : Objective: The aim of this study was to investigate everolimus efficacy in well-moderately differentiated pancreatic NEC (pNEC) G3. Methods: This was a retrospective analysis of patients with pNEC G3 and Ki67 20% to 55% treated with everolimus. Results: Fifteen patients with median Ki67 30% and Eastern Cooperative Oncology Group performance status 0 to 1 were evaluated. Of these, 4 patients received everolimus as first-line treatment, whereas 11 had been pretreated with chemotherapy or peptide receptor radionuclide therapy. Median progression-free survival was 6 months, and median overall survival was 28 months. Eleven patients achieved disease stabilization (DS) at 3 month follow-up. Six patients (40%) maintained DS for at least 12 months. Three of 4 patients who received everolimus as first-line therapy had sustained DS (progression-free survival, 12, 17, and 22 months). The safety profile was consistent with that previously reported, with adverse events occurring in 9 patients (66.7%). Conclusions: This study suggests that everolimus is active in pNEC G3 with well-moderately differentiated morphology and Ki67 less than 55%, in which more toxic systemic chemotherapy is, to date, the only available treatment.